Antiviral abilities of Curcuma kwangsiensis ingredients against grouper iridoviral infection in vitro and in vivo. (6th November 2019) - Liu, Mingzhu; Xiao, Hehe; Zhang, Qin; Wu, Siting; Putra, Dedi Fazriansyah; Xiong, Xiangying; Xu, Mingzhu; Dong, Lanfang; Li, Siqiao; Yu, Qing; Li, Pengfei
Abstract: As one of the most serious pathogens in mariculture, the outbreaks of grouper Iridovirus (SGIV‐Gx) caused high mortality rates in cultured groupers in Guangxi, China. Hence, effective medicines for fighting against grouper Iridovirus are urgently needed. The possible application of Curcuma kwangsiensis ingredients against SGIV‐Gx infection was evaluated in vitro and in vivo in this study. The safe working concentration of each C. kwangsiensis ingredient was identified ( C. kwangsiensis ethanol ingredient, CKEE ≤5 mg/ml; curcumin ≤20 μg/ml; curdione ≤500 μg/ml; curcumenol ≤500 μg/ml; curcumol displayed no cytotoxic effects even at 2 mg/ml) in vitro and in vivo. The inhibitory activities of each C. kwangsiensis ingredient against SGIV‐Gx infection were analysed using aptamer (Q2)‐based fluorescent molecular probe (Q2‐AFMP) and RT‐qPCR. The results showed that C. kwangsiensis ingredient (CKEE, curcumin, curcumol, curdione and curcumenol) displayed antiviral activities against SGIV‐Gx infection in a dose‐dependent manner. Furthermore, according to the inhibitory percentage analysed using RT‐qPCR results, CKEE and curdione had the best antiviral activity against SGIV‐Gx above 93%. Overall, the results suggest that some C. kwangsiensis ingredients have excellent antiviral effects, making it an interesting candidate for developing effective medicines for preventing and controlling SGIV‐Gx outbreaks in mariculture.